Health care‐associated infections after major cancer surgery. Issue 12 (19th March 2013) - Sammon, Jesse; Trinh, Vincent Q.; Ravi, Praful; Sukumar, Shyam; Gervais, Mai‐Kim; Shariat, Shahrokh F.; Larouche, Alexandre; Tian, Zhe; Kim, Simon P.; Kowalczyk, Keith J.; Hu, Jim C.; Menon, Mani; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Approximately 1.7 million individuals per year are affected with health care‐associated infections (HAIs) in the United States. The authors examined trends in the incidence of HAI after major cancer surgery (MCS) and risk factors for HAI to describe the effects of HAI on mortality after MCS. METHODS Patients undergoing 1 of 8 MCS procedures within the Nationwide Inpatient Sample between 1999 and 2009 were identified (n = 2, 502, 686). Generalized linear regression models were used to estimate the impact of the primary predictors (procedure type, age, sex, race, insurance status, Charlson comorbidity index, hospital volume, and hospital bed size) on the odds of HAI and in‐hospital mortality. Trends in incidence were evaluated with linear regression. RESULTS Overall, MCS‐associated HAI incidence increased 2.7% per year (P < .001), whereas mortality decreased 1.3% per year (P < .001). Male gender (odds ratio [OR], 1.12, 95% confidence interval [CI], 1.10‐1.14), advancing age (OR, 1.02; 95% CI, 1.02‐1.02), black race (OR, 1.26; 95% CI, 1.21‐1.31), ≥1 comorbidities (OR, from 1.08 [95% CI, 1.04‐1.13] to 1.31 [95% CI, 1.27‐1.35]), and nonprivate insurance (OR, from 1.18 [95% CI, 1.15‐1.22] to 1.67 [95% CI, 1.59‐1.76]) were associated with an increased odds of HAI on multivariable analysis. Conversely, increasing hospital volume was associated with lower odds of HAI (OR, 0.999; 95% CI, 0.99‐0.99). Patients with MCS‐associated HAI had increased odds of mortality (OR, 8.66; 95% CI, 8.51‐8.82). CONCLUSIONS Between 1999 and 2009, the incidence of MCS‐associated HAI events increased; however, HAI‐associated mortality decreased. That said, significant disparities exist in the hospital and demographic attributes associated with MCS‐associated HAI, with attendant health policy implications. Moreover, HAI remains detrimentally linked to mortality during hospitalization. Cancer 2013;119:2317–2324. © 2013 American Cancer Society.